Labour market polarization in South Africa: A decomposition analysis - Robert H. Davies; Dirk van Seventer (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
There is evidence from developed countries that technical change affects not only the employment intensity of production, but also the occupational composition of employment. The use of artificial intelligence, automation, and robots has changed the skills composition of employment. A range of 'routine' tasks are being replaced by machines which has led to polarization: a relative increase in higher level and in lower level jobs. This paper is concerned with examining the extent to which labour market polarization has taken place in South Africa over the period 1993-2017. A decomposition method is used in which change in employment can be attributed to changes in occupational mix, technology, and economic structure as well as an economic growth effect. The polarization we find is mild. This may be because technology in South Africa lags elsewhere. Furthermore, the low rates of investment in South Africa means that uptake of new technology is slow.
Keywords: J21; J24; C65; 330; decomposition; labour market; polarization; tasks; occupations